The health care home in New Zealand: rolling out a new model of primary health care. Issue 3 (14th June 2018) - Cumming, Jacqueline; Dunn, Phoebe; Middleton, Lesley; O'Loughlin, Claire
Abstract : Purpose: The purpose of this paper is to report on the origins, development and early impacts of a Health Care Home (HCH) model of care being rolled out around New Zealand (NZ). Design/methodology/approach: This paper draws on a literature review on HCHs and related developments in primary health care, background discussions with key players, and a review of significant HCH implementation documents. Findings: The HCH model of care is emerging from the sector itself and is being tailored to local needs and to meet the needs of local practices. A key focus in NZ seems to be on business efficiency and ensuring sustainability of general practice – with the assumption that freeing up general practitioner time for complex patients will mean better care for those populations. HCH models of care differ around the world and NZ needs its own evidence to show the model's effectiveness in achieving its goals. Research limitations/implications: It is still early days for the HCH model of care in NZ and the findings in this paper are based on limited evidence. Further evidence is needed to identify the model's full impact over the next few years. Originality/value: This paper is one of the first to explore the HCH model of care in NZ.